CHRIS ROCK, FROM COMEDY TO TRAGEDY: PHENOMENON ON OSCAR 2022 STAGE - Lambok Hermanto Sihombing; Maria Paskalia Aninda (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
This study aims to analyze the phenomenon at the 2022 Oscars. The origin of this issue is the tragic joke-turned-tragic slapping by Chris Rock. This research utilized a descriptive qualitative methodology. The primary source for this study was content analysis data from Oscar 2022, when Chris Rock hosted. This research's objective was determined in three steps: data gathering from YouTube and Instagram channels, data analysis, and discussion and results. After all the data was collected, the researchers tried to find the theory of superiority and underestimation in Gauter (1988) as the situation showed how Chris Rock used Jada Pinkett as a joke. Based on data analysis, the researchers determined that the OSCAR 2022 case study was separated into the following sections: The context of comedy, Moral power, and code of ethics on stage. Based on the analysis results, the researchers found out that the most important takeaway from this topic is that not everything is appropriate and worthy of being converted into a joke, much alone entertaining the public.